Measuring the sensitivity of Staphylococcus aureus membranes to antimicrobial peptides under oxygen-restricted growth conditions (2024)
Staphylococcus aureus is an opportunistic pathogen that has shown rapid adaptation through environmental stress. The irresponsible usage of antibiotics has created resistant strains and is a major problem according to the World Health Organization. In living organisms, there have been found small proteins that have antibacterial activity. These are known as antimicrobial peptides (AMPs). In the current study, LL-37, a human cathelicidin, is tracked into binding and leakage activity in the presence of S. aureus membranes. Cultures were grown under rich-oxygen and oxygen-restricted conditions, triggering aerobic/anaerobic respiration and changes in the biophysical properties of the membrane. Measuring -potential, binding, and leakage with fluorescence techniques, we characterized the behavior of LL-37. Results showed that S. aureus is stronger than model membranes, and has resistance to the AMP rather because of its charge or the presence of carotenoids. -potential measurements from S. aureus were far more negative than expected. This could be due to the presence of teichoic acid on the membranes or oxidation processes induced in the measurement. To complete the research, it is proposed to repeat the experiment from exponential growth lipid extractions, use a common cationic AMP: Atra-1, and induce knockout to staphiloxatin production in aerobic cultures.